Protein supplementation associated with resistance exercise to reduce the sarcopenia process in aging (Research, Society and Development, 2025)
Sarcopenia is defined as a geriatric syndrome in which there is progressive and generalized loss of muscle mass, associated with reduced strength and function of skeletal muscles. In this sense, a targeted nutritional intervention can prevent negative protein balance and subsequent muscle catabolism, associated with resistance exercises, there is a greater stimulation of protein synthesis in skeletal muscle. The objective of this study is to evaluate the effects of protein supplementation associated with the practice of physical exercises to reduce sarcopenia. This work is a bibliographic review, in which searches were carried out in databases such as MEDLINE, LILACS, BVS, as inclusion criteria, articles published between 2010 and 2025, written in Portuguese and English, were used. In the 10 randomized clinical trials that were analyzed, it was found that the association of a diet with a higher protein content and the practice of resistance physical exercises is a potentially effective tool for the treatment of geriatric syndrome, sarcopenia.